MUTASI YANG BERKEADILAN DALAM HUBUNGAN KERJA - ginting, sryani; Tobing, Christina NM. (Citra Justicia : Majalah Hukum dan Dinamika Masyarakat, 2024)
In many workplaces, workers often reject job mutations, leading to disputes with employers. This article aims to examine the issue of job mutations in the context of labor relations from a justice perspective. The study uses a descriptive analytical method with a normative legal approach. The normative legal approach is used to analyze secondary data in the form of regulations and several decisions from the Industrial Relations Court that have become legally binding, selected through a purposive sample. The data analysis is qualitative. The research results show that job mutations are the employer's right for various purposes and reasons. Mutations must be fair, namely taking into account the suitability of the worker's competence, skills, expertise, interests, talents and abilities while paying attention to dignity, human rights and legal protection. Resolving disputes is in line with the mechanisms regulated by Law No. 2 of 2004 on the Settlement of Industrial Relations Disputes, which includes non-litigious and litigious methods. The problem is that some decisions from the Industrial Relations Court, judges provide different interpretations and applications of the law regarding the rejection of job mutations, as job mutations are not regulated in the Labor Law, thus failing to achieve justice, benefits, and legal certainty. Unfair mutations can be used by employers as a means to carry out layoffs on the grounds that they are qualified to resign in accordance with Article 154A paragraph (1) letter j of the Employment Law, while also eliminating the obligation to pay severance pay and long service bonus money. The rejection of job mutations is also interpreted as a violation of company regulations, leading to termination of employment according to Article 154A paragraph 1 letter k. Job mutations without considering human dignity will be considered as termination of employment due to efficiency according to Article 154A paragraph 1 letter b. Job mutations between companies with different legal entities are termination of employment, which can be used according to Article 154A paragraph 1 letter a. Fair job mutations require workers to implement job mutations. Fair job mutations will minimize disputes and improve worker morale, loyalty, and performance, ultimately advancing the company.